1970
DOI: 10.4314/evj.v20i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Sero-prevalence status of foot and mouth disease in the North Western Amhara Regional State, Ethiopia

Abstract: A cross-sectional survey was conducted on serum samples collected from North and South Gondar zones of North Western Amhara Regional State, Ethiopia to determine the sero-prevalence of foot and mouth diseases in bovine species. The samples were processed with the nonstructural protein (NSP) enzyme linked immunosorbent assay (ELISA) that can able to differentiate foot and mouth disease (FMD) naturally infected vaccinated animals. From the total sera tested, the overall sero-prevalence of foot and mouth disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
3
2
2
Order By: Relevance
“…Similarly, in previous studies, conducted in central Ethiopia, crossbred cattle were 2.79 times more likely than local cattle to seropositivity of the disease (14), and in another study from West Shewa Zone, Ethiopia, crossbred cattle were 6 times more likely than local cattle in seropositivity (15). In this study, the sex group was not statistically signi cant and it was in agreement with many previous studies ( 16); (8); (12).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, in previous studies, conducted in central Ethiopia, crossbred cattle were 2.79 times more likely than local cattle to seropositivity of the disease (14), and in another study from West Shewa Zone, Ethiopia, crossbred cattle were 6 times more likely than local cattle in seropositivity (15). In this study, the sex group was not statistically signi cant and it was in agreement with many previous studies ( 16); (8); (12).…”
Section: Discussionsupporting
confidence: 92%
“…in addition, it may be due to exporting of animals than importing in the area. In the south Gondar Zone districts, Tesfaye and his colleagues reported that the prevalence of the disease in the area was 9.6% (12). However, it was 3.6% in the current study; this may be due to variations in selected peasant associations.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Uterine paresis, abortion, stress, late or premature birth, dystocia, twinning, infections, seasonal and hormonal disorders, immune suppression vitamin, and mineral deficiencies have been identified as causes of RFM by Beagley, et al [41]. In this study, the prevalence of clinical FMD (16.5%) was lower than the reports done by Misgana, et al [42] in Bale (two districts and one dairy farm) was 21.59% and Tesfaye [43] who reported the prevalence done 21% in Borana pastoral area. Additionally, at the animal level, the prevalence of the current study (9.2%) was lower than the results (17.7%) by Haftu, et al [44] in Eastern Zone of Tigray, Ayelet, et al [45] in Guji zone in Oromia (32.7%) and Yeka district of Addis Ababa, with the prevalence of 30%.…”
Section: The Major Health Problems and Constraints In Farms In And Ar...contrasting
confidence: 51%
“…There is strong agreement with the findings of Megerssa et al (35) and Mesfine et al (27), who reported that animals found in midlands and highlands were 83% (OR = 0.17, CI = 0.04-0.85) less likely to be seropositive for FMD than lowland animals. Similarly, Tesfaye et al (42) found significant differences between areas of different altitudes with a prevalence of 53.6% and 10.1% at low and high altitudes, respectively. This prevalence variation arises due to an increase in exposure of animals to the putative risk factors in lowland areas.…”
Section: Seroprevalence and Associated Risk Factors Of Fmdmentioning
confidence: 85%